2015
DOI: 10.1212/wnl.0000000000001240
|View full text |Cite
|
Sign up to set email alerts
|

Colonic mucosal α-synuclein lacks specificity as a biomarker for Parkinson disease

Abstract: Objective: To determine the utility of detecting a-synuclein (aSyn) in colonic mucosal biopsy tissue as a potential diagnostic biomarker for Parkinson disease (PD). Methods:We used the paraffin-embedded tissue (PET) blot, which degrades physiologic nonaggregated aSyn using proteinase K and enhances antigen retrieval allowing sensitive and selective detection of remaining protein aggregates, to detect aSyn in colonic mucosal biopsies from 15 patients with early PD (,3 years), 7 patients with later PD (.5 years)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
145
3
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 136 publications
(158 citation statements)
references
References 28 publications
(41 reference statements)
7
145
3
3
Order By: Relevance
“…Each technique is specific for a particular variant or conformation of aSyn. For IHC, antibodies reactive for total (T‐aSyn‐Ab) and phosphorylated (P‐aSyn‐Ab) aSyn were selected as they have been most widely used for the detection of aSyn in the GI tract making our results comparable with these previous studies 4, 14, 15, 17, 19, 20. We also used recently developed antibodies specific for the oligomeric forms of aSyn (O‐ASN‐Abs) 26, as transformation of monomeric aSyn to oligomeric conformations is increasingly recognized as the early, key pathological event in the fibrillization process of aSyn 27.…”
Section: Introductionsupporting
confidence: 53%
See 3 more Smart Citations
“…Each technique is specific for a particular variant or conformation of aSyn. For IHC, antibodies reactive for total (T‐aSyn‐Ab) and phosphorylated (P‐aSyn‐Ab) aSyn were selected as they have been most widely used for the detection of aSyn in the GI tract making our results comparable with these previous studies 4, 14, 15, 17, 19, 20. We also used recently developed antibodies specific for the oligomeric forms of aSyn (O‐ASN‐Abs) 26, as transformation of monomeric aSyn to oligomeric conformations is increasingly recognized as the early, key pathological event in the fibrillization process of aSyn 27.…”
Section: Introductionsupporting
confidence: 53%
“…neuritic and ganglionic ) were considered to be specifically neuronal and putatively pathological. Different antibodies showed drastically different sensitivities (and specificities) for the neuronal pattern of staining, with the highest sensitivity being achieved with the O‐aSyn‐Ab, with a positive signal in 39% of PD vs. 24% HC, followed by the P‐aSyn‐Ab with 14% of PD vs. 24% HC, and finally T‐aSyn‐Ab that surprisingly, and in contrast with other studies 4, 15, 19, 20, 33 showed no neuronal staining in any of the examined cases. We found no difference in specificity whether we used O/P‐aSyn‐Ab.…”
Section: Discussionmentioning
confidence: 68%
See 2 more Smart Citations
“…However, "pathological" α-synuclein species have been detected in the gut of healthy asymptomatic ageing adults (39,40,41,42). Early studies of the GI tract in Parkinson's disease reported Lewy bodies and neurites comparable to those observed in brain (43,44,45).…”
Section: Accumulation Of α-Synuclein In Enteric Neurons After Organotmentioning
confidence: 99%